The prevalence of cholelithiasis in Nigerians with sickle cell disease as diagonosed by ultrsound (2014)
Aim: To determine the prevalence of cholelithiasis in Nigerians with sickle cell disease in steady state, using ultrasonography. Study design: A prospective cross-sectional study. Place and duration of study: Haematology clinic, University of Benin Teaching Hospital, Benin city and Sickle Cell Centre, Benin city, Nigeria between July and December, 2011. Methodology: The study population was made up of non-pregnant sickle cell disease patients not in crisis and who have not had cholecystectomy. They were confirmed to have sickle cell disease through haemoglobin electrophoresis. All the patients were examined with a B- mode ultrsound machine with a curvilinear multifrequency transducer 2.5-7.5 MHZ after an overnight or at least six hour fast. Calculi were diagnosed if highly echnogenic structures, with acostic shadowing were deleted in the lumen of the gallbladder. Results: There were 79 females and 71 males, aged between 10 months and 51 years. Of the 150 patients, 140 were homozygous for sickle cell disease (HbSS), while the remaining 10 were heterozygous for sickle cell disease (HbSC). The prevalence of cholelithiasis was 16.0%. It was related to age , sex and haemoglobin genotype. There was progressive increase in cholelithoasis with age which was more pronouced in the third and fourth decades. Cholelithiasis was also significantly more commonly seen in the HbSS group 23 (16.4%) out of 140 patients compared wth the HbSC group 1 (10.0%) out of 10 patients. Cholelithiasis did not correlate with sex, althoguh it was more commonly observed in females. The youngest patient with gall stones in this study was 2 years. Conclusion: The prevalence of cholelithiasis in Nigerians with sickle cell disease was 16.0% and it was related to age and haemoglobin genotype.